Risk factors associated with musculoskeletal disorders in family farming: A literature review - Calvo-Solano, Oscar David (2019)
This work seeks to study the risk factors associated with the onset of musculoskeletal disorders (MSDs) in workers dedicated to family farming, based on a literature review of the databases available in the Library, Documentation and Information System of the Universidad de Costa Rica (whose acronym in Spanish is SIBDI-UCR) for the period 2012-2018, to make recommendations for preventing the occurrence of MSDs. Nineteen (19) scientific articles were selected, which were subjected to both a frequency analysis and a social network analysis. It was found that inappropriate posture, lifting and transporting heavy loads, age, repetitive tasks, years of experience, and sex are the main risk factors associated with the appearance of MSDs in the lower back, shoulders and knees, which are the main disorders that affect family farm workers. It is concluded that it is necessary to develop strategies for preventing these factors and disorders, as well as educational processes that contribute to the reduction of different risks in this population.